2011
DOI: 10.4103/1119-3077.86772
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypertension amongst persons with diabetes mellitus in Benin City, Nigeria

Abstract: Hypertension is prevalent in persons with DM. Studies have shown that adequate control of the blood pressure reduces the microvascular and macrovascular complications of DM. DM care providers must prescribe appropriate antihypertensive therapy to control hypertension in persons with DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
54
5
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 13 publications
9
54
5
2
Order By: Relevance
“…It is therefore not surprising that over 40% of the participants in our study were hypertensive. This has been observed in several studies conducted in Ghana [2], [40], [41] and several other countries [42], [43], [44].…”
Section: Discussionsupporting
confidence: 69%
“…It is therefore not surprising that over 40% of the participants in our study were hypertensive. This has been observed in several studies conducted in Ghana [2], [40], [41] and several other countries [42], [43], [44].…”
Section: Discussionsupporting
confidence: 69%
“…A study among diabetic patients in Nigeria found the prevalence of hypertension to be 54.2%, consistent with another research conducted in the United States of America that established a high hypertension prevalence rate of 59.4% among diabetic patients . According to Shah and Afzal, coexistence of hypertension and diabetes increases the risk of cardiovascular diseases by about 75.0% with a subsequent rise in total morbidity and mortality.…”
Section: What Is Known and Objectivesupporting
confidence: 81%
“…The recent EPIDIAM Study conducted in 525 type 2 diabetic individuals in three Moroccan regions reported that 70.4% of the individuals had HTN [69]. Another study conducted in Benin City, Nigeria, reported that 54.2% of the diabetic individuals had HTN [70]. …”
Section: Coexistence Of Diabetes and Hypertensionmentioning
confidence: 99%